Microstructure and Wear Behavior of Plasma‐Sprayed Nanostructured WC–Co Coatings. Issue 1 (17th January 2012) - Di Girolamo, Giovanni; Marra, Francesco; Pilloni, L.; Pulci, Giovanni; Tirillò, Jacopo; Valente, Teodoro
<x xml:space="preserve">Abstract</x> Atmospheric plasma spraying of WC–Co particles with standard gas mixtures (Ar–H2) typically results in largely decarburized coatings with relatively low wear resistance. To fabricate cermet coatings with enhanced tribological properties, nanostructured WC–Co coatings were plasma sprayed using two different process gas mixtures. Phase composition and microstructure were investigated by X‐ray diffraction and scanning electron microscopy, respectively. Microhardness increased by increasing the amount of retained WC grains in coating microstructure. Friction and wear properties, measured under dry sliding conditions, strongly depended on the degree of decarburization. They were comparable to those of conventional coatings produced using identical conditions.